Combinatorial control of DNase I-hypersensitive site formation and erasure by immunoglobulin heavy chain enhancer-binding proteins. - Ishii, H.; Sen, R.; Pazin, M.J. (Journal of Biological Chemistry, 2004)
DNase I-hypersensitive sites in cellular chromatin are usually believed to be nucleosome-free regions generated by transcription factor binding. Using a cell-free system we show that hypersensitivity does not simply correlate with the number of DNA-bound proteins. Specifically, the leucine zipper containing basic helix-loop-helix protein TFE3 was sufficient to induce a DNase I-hypersensitive site at the immunoglobulin heavy chain micro enhancer in vitro. TFE3 enhanced binding of an ETS protein PU.1 to the enhancer. However, PU.1 binding erased the DNase I-hypersensitive site without abolishing TFE3 binding. Furthermore, TFE3 binding enhanced transcription in the presence and absence of a hypersensitive site, whereas endonuclease accessibility correlated strictly with DNase I hypersensitivity. We infer that chromatin constraints for transcription and nuclease sensitivity can differ.